1987
DOI: 10.1063/1.339174
|View full text |Cite
|
Sign up to set email alerts
|

Optical and electronic properties of vanadium in gallium arsenide

Abstract: Gallium arsenide as an optical strain gauge Rev.The effects of vanadium doping on the electrical and optical properties of GaAs were systematically studied in melt-grown crystals prepared by the liquid-encapsulated Czochralski and horizontal Bridgman techniques and in epitaxial crystals prepared by liquid-phase electroepitaxy. By employing deep-level transient spectroscopy, Hall-effect measurements and the V2+ (3d 3) and V3+ (3d 2) intracenter optical-absorption spectra, one vanadium-related level was identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Hennel et al [2] concluded that in vanadium-doped GaAs subtle chemical background effects, such as gettering, lowered the concentration of residual donors and improved the material electronic properties. A high concentration of magnetic ions, such as Mn, could lead to novel semiconductor materials with specific magnetic and electronic properties-diluted magnetic semiconductors [3].…”
Section: Introductionmentioning
confidence: 99%
“…Hennel et al [2] concluded that in vanadium-doped GaAs subtle chemical background effects, such as gettering, lowered the concentration of residual donors and improved the material electronic properties. A high concentration of magnetic ions, such as Mn, could lead to novel semiconductor materials with specific magnetic and electronic properties-diluted magnetic semiconductors [3].…”
Section: Introductionmentioning
confidence: 99%
“…Vanadium doped, semi-insulating GaAs crystals were prepared by the liquid encapsulated Czochralski (LEC) technique with a vanadium concentration of 7=8 x 10 16 cm -3 [10]. Zero pressure luminescence was measured in a CF1204 (Oxford) cryostat.…”
Section: Methodsmentioning
confidence: 99%
“…This information guides to the assignment of the emission band. The nature of vanadium doping related defects have been the object of different experimental studies [14][15][16]. In III-V compounds, the transition metals are usually incorporated on substitutional cation sites.…”
Section: Methodsmentioning
confidence: 99%